Plectania lutea (Sarcosomataceae), a new species from southwestern karst areas of China - Mou, Guang-Fu; Bau, Tolgor (Phytotaxa, 2021)
Plectania lutea, is described as a new species from subtropical karst areas of China. The main distinguishing characteristics of P. lutea are the yellow hymenium, the external surface with ridges, the gelatinous but not semifluid medullary excipulum, and the large finely warted ascospores. The phylogenetic analyses based on internal transcribed spacer (ITS) and the large subunit (LSU) regions of rDNA sequences using Bayesian (BA) and Maximum Likelihood (ML) methods showed that the new taxon can be distinguished from phenotypically similar and phylogenetically related species.